To the taxonomy of Rhodiola L. (Crassulaceae DC.) of the Russian Far East - V. V. Yakubov (Проблемы ботаники Южной Сибири и Монголии, 2019)
The results of the taxonomic revision of the genus Rhodiola L. (Crassulaceae DC.) of the Russian FarEast are discussed. There are currently 7 known species of Rhodiola in this area: Rh. rosea L., Rh. integrifolia Raf., Rh.×borealis Boriss., Rh. quadrifida (Pall.) Fisch. et C.F. Mey., Rh. angusta Nakai, Rh. stephanii (Cham.) Trautv. et Mey.,Rh. ishidae Hara. Rh. krivochizhinii Sipl. and Rh. sachalinensis Boriss. described from Verkhoturov Island and SakhalinIsland do not have explicit taxonomic differences from Rh. rosea and should be regarded as its synonyms.